2010
DOI: 10.1504/ijtm.2010.032677
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and coordination: what is the contribution of a proximity-based analysis? The case of Airbus and its relations with the subcontracting network

Abstract: In this paper, we propose to expound the various dimensions of proximity with a view to emphasizing the institutional and organizational dimensions of inter-firm relations. To that end, we set out to define, in a first part, the various forms of geographic, institutional and organizational proximity, and to put them into perspective. The dual role of geographic proximity as a source of conflicts and resource for collective action is underlined. We then intend to show that the institution generates a so-called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 8 publications
0
11
0
5
Order By: Relevance
“…From this plot we can already detect how the Campania cluster extends beyond its territorial boundaries through consolidation of relationships between Alenia Aeronautica and foreign system integrators, thus following a well-established pattern for the aeronautics sector (Biggiero and Samarra, 2010;Kechidi and Talbot, 2010). However, more accurate analysis of the relationships makes it clear that the international relationships are concentrated on Alenia, and that the other firms in the region have relationships with foreign companies only through the single large Campania firm.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…From this plot we can already detect how the Campania cluster extends beyond its territorial boundaries through consolidation of relationships between Alenia Aeronautica and foreign system integrators, thus following a well-established pattern for the aeronautics sector (Biggiero and Samarra, 2010;Kechidi and Talbot, 2010). However, more accurate analysis of the relationships makes it clear that the international relationships are concentrated on Alenia, and that the other firms in the region have relationships with foreign companies only through the single large Campania firm.…”
Section: Resultsmentioning
confidence: 88%
“…By applying network analysis and gathering opinions through interviews, we have shown that Alenia Aeronautica can be identified as the central firm of the cluster, but that it is unable to completely fulfill its role as anchor tenant. The literature has described several recent trends in the aeronautics industry, which also seem very evident in the Campania cluster: i) greater fragmentation among the various actors in the production chain (Kechidi & Talbot, 2010); ii) continually greater interdependence among the various actors, which favors the birth of relationship networks that go beyond national borders, to unite clusters and firms that operate in very distant geographic areas (Biggiero & Samarra, 2010); iii) attention to innovation, in part through interaction with the new materials sector and other sectors (Benzler & Wink, 2010). Faced with these phenomena, Alenia does not seem to have taken an adequate role.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These explorations also deal with the issues of institutional dynamics, expressed through the analysis of the modes, of the causes and effects of the processes of institutional innovation on the coordination between actors and the dynamics of local development. Let us note that other analyses, focusing on the very definition of proximity, see in the latter a profoundly institutional phenomenon (Kechidi and Talbot, 2010).…”
Section: A Variant School Of Thought That Considers That the Politicamentioning
confidence: 93%